(untitled) - Chih-hsing, Huang (Hong Kong, 1955)
Very hard to find book advertised as "The First Comprehensive and Objective Study of Chinese Psychological Warfares." Pages are tanned with age and show mild soil. Scarce original dust jacket present though showing wear and tear. We've given the jacket a new archival clear sleeve to protect it from further wear. Sturdy gray hardcover binding with black stamped front cover design.
Keywords: Chiến tranh tâm lý,Psychological warfare